Pulse chaotic generator based a classical Chua’s circuit - Rusyn, Volodymyr; Samila, Andrii; Markovych, Bogdan; Sambas, Aceng; Skiadas, Christos; Guzan, Milan (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
This article presents circuit realization of the pulse chaotic generator that can be used in digital modern telecommunication systems for masking and decrypt of the information. This generator based a classical Chua’s circuit. The results of computer simulation of a nonlinear element that realizes the chaotic behavior of the classical Chua’s circuit are presented. For modelling was used a modern software MultiSim. Also, such basic results as chaotic attractor and time distributions of signals were obtained.